Catch And Composition Of Tuna Longline Landed On Bungus Fishing Port - Gustiana Putri; Arthur Brown; Bustari Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on juni 2018 in  Bungus samudera fishing port. The purpose of this research was to know the composition of main catch and by-catch tuna longline and hook rate of tuna longline based at Bungus samudera fishing port. The method used in this research is survey method. The data analysis  using composition analysis and hook rate. The using data are catched of longline data on 2015-2016 in  Bungus samudera  fishing port.  From this research obtained of main catch as much 4 spesies consists of Big eye tuna, Madidihang, Albakor and Blue fin tuna and by-catch as much 16 spesies obtained of Setuhuk loreng, setuhuk hitam, pedang, mackerel, angelfish, lisong, skipjack tuna, lemadang, mackerel tuna, marlin fish, meka fish, todak fish, stingray, and shark. Hook rate obtained of main catch in this research are Albakor 0,05, Bigeye tuna 0,12, Madidihang 0,27 and Blue fin tuna 0,01. This hook rate was so little or decline who indication happening of exploitation in Samudera Hindia. Keyword: longline, hook rate, composition of catc